In situ liver transection with portal vein ligation for rapid growth of the future liver remnant in two‐stage liver resection. Issue 3 (2nd November 2012) - Knoefel, W. T.; Gabor, I.; Rehders, A.; Alexander, A.; Krausch, M.; Schulte am Esch, J.; Fürst, G.; Topp, S. A.
Abstract Background: Portal vein embolization (PVE) has become a standard procedure to increase the future liver remnant (FLR) and enable curative resection of initially unresectable liver tumours. This study investigated the safety and feasibility of a new two‐stage liver resection technique that uses in situ liver transection (ISLT) and portal vein ligation before completion hepatectomy. Methods: A consecutive series of patients undergoing ISLT and extended right hepatectomy between 2009 and 2011 were compared with consecutive patients undergoing extended right hepatectomy after PVE. All patients had initially unresectable primary or secondary liver tumours, owing to an insufficient FLR (liver segments II/III). Results: Fifteen patients who had PVE and seven who underwent ISLT before extended right hepatectomy were evaluated. ISLT induced rapid growth of the FLR within 3 days, particularly after insufficient PVE, from a mean(s.d.) of 293(58) ml to 477(85) ml, corresponding to a volume increase of 63(29) per cent. All patients who had ISLT underwent completion extended right hepatectomy within 8 days (range 4–8 days). Conclusion: ISLT is an effective and reliable technique to induce rapid growth of the FLR, even in patients with insufficient volume increase after PVE. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.